Pengaruh Edukasi Video Animasi terhadap Kepatuhan Minum Obat dan Tekanan Darah pada Pasien Hipertensi di Rumah Sakit Islam Sultan Agung Semarang - Icha Boy Rantau; Indah Sri Wahyuningsih; Mohammad Arifin Noor (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a chronic disease that requires long-term medication adherence to prevent more serious complications. However, there is still a high level of non-compliance among hypertension patients, which may worsen their condition. One way to improve compliance is through health education based on animated videos, which can enhance patients' understanding and motivation. This study aims to analyze the effect of animated video education on medication adherence and blood pressure control in hypertensive patients at Sultan Agung Islamic Hospital Semarang. The study used a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 38 respondents selected through purposive sampling, divided into two groups: the intervention group (n=19) and the control group (n=19). The intervention group received animated video education, while the control group only underwent observation. Adherence was measured using the MMAS-8 questionnaire, and blood pressure was measured using a sphygmomanometer. Data analysis was performed using the Wilcoxon, McNemar, and Mann-Whitney tests to examine differences between groups. The results showed a significant increase in medication adherence and a reduction in both systolic and diastolic blood pressure in the intervention group compared to the control group (p<0.05). These findings suggest that animated video education is effective in improving medication adherence and helping control blood pressure in hypertensive patients. Therefore, animated video education can be recommended as a nursing education strategy to improve medication adherence and hypertension management.